Therapeutic Applications of Physalins: Powerful Natural Weapons - Meira, Cássio Santana; Soares, José Waldson Capinan; dos Reis, Bruna Padilha Zurita Claro; Pacheco, Luciano Vasconcellos; Santos, Ivanilson Pimenta; Silva, Dahara Keyse Carvalho; de Lacerda, Julia Costa; Daltro, Sérgio Ricardo Teixeira; Guimarães, Elisalva Teixeira; Soares, Milena Botelho Pereira (Frontiers in Pharmacology, 2022)
Physalins, or 16,24-cyclo-13,14-seco steroids, are compounds belonging to the class of withanolides that can be found in plants of Solanaceae family, mainly in species belonging to the genus Physalis spp., which are annual herbaceous plants widely distributed in tropical and subtropical regions of the world. Physalins are versatile molecules that act in several cell signaling pathways and activate different mechanisms of cell death or immunomodulation. A number of studies have shown a variety of actions of these compounds, including anticancer, anti-inflammatory, antiparasitic, antimicrobial, antinociceptive, and antiviral activities. Here we reviewed the main findings related to the anticancer, immunomodulatory, and antiparasitic activities of physalins and its mechanisms of action, highlighting the challenges and future directions in the pharmacological application of physalins.